Use of the greater palatine pedicled flap for the surgical management of trismus in oral submucous fibrosis. Issue 8 (October 2021) - Shadamarshan R, Arunkumar; Sharma, Rohit; Grewal, Ritu; Patrikar, Seema
Abstract: The aim of this paper was to clinically evaluate the efficacy of the greater palatine pedicled flap (GPPF) for the correction of trismus in oral submucous fibrosis (OSMF). This retrospective study was designed from the patients diagnosed with OSMF who underwent transection of fibrous bands and coverage of the defect in the retromolar trigone (RMT) region using GPPF from 2008-2019. Cases were analysed for preoperative (MOpre-op ), and postoperative mouth opening (MOpost-op ), secondary healing of the palate, and complications of the procedure. A total of 29 diagnosed cases of OSMF were divided into two groups: group I/stage III (n=13) and group II/stage IV (n=16). The mean (SD) follow up was 29.6 (2.92) months for Group I and 32.4 (3.54) months for Group II. Increase in MOpost-op in group I from 20.0 to 32.92 mm (p=0.0001) and in group II from 6.81 to 26.31 (p=0.0001) was statistically significant. The mean difference of 6.57 mm in MOpre-op and MOpost-op among the groups was also statistically significant (p=0.0001). The mean (SD) duration for secondary healing of the palate was 5 (1) week(s) and flap necrosis was encountered in two cases of group II/stage IV OSMF. We conclude that GPPF is reliable for the treatment of trismus in advanced stages of OSMF.